Hiding from reality by harming others: on the groundlessness of victim blaming and its correlation with violence (Balthazar, 2021)
Unconsciously trying to defend ourselves from violence and fear, we often resort to simplistic and unsubstantiated explanations whose only goal is to make complex situations easier to deal with. This is the case of victim blaming. In order to defend what according to Lerner is our conception of a just world, we tend to blame those who have suffered violence or misfortune to obviate the possibility of being the object of it. If negative situations depend directly on those who have suffered them, then it becomes easier for others to save themselves. It is the convenience of the simplistic explanation, its being reassuring and enveloping, that often leads us to resort to it. But what are the consequences of this type of attitude? This paper aims to show these consequences, revealing the correlation between victim blaming and violence. In particular, we will analyze victim blaming underlining its groundlessness starting from some rape cases.
Keywords: victim blaming; violence; bias